Clodronate liposomes improve metabolic profile and reduce visceral adipose macrophage content in diet-induced obese mice. - Bin Feng (PLoS ONE, 2011)
BACKGROUND: Obesity-related adipose inflammation has been thought to be a causal factor for the development of insulin resistance and type 2 diabetes. Infiltrated macrophages in adipose tissue of obese animals and humans are an important source for inflammatory cytokines. Clodronate liposomes can ablate macrophages by inducing apoptosis. In this study, we aim to determine whether peritoneal injection of clodronate liposomes has any beneficial effect on systemic glucose homeostasis/insulin sensitivity and whether macrophage content in visceral adipose tissue will be reduced in diet-induced obese (DIO) mice. METHODOLOGY/PRINCIPAL FINDINGS: Clodronate liposomes were used to deplete macrophages in lean and DIO mice. Macrophage content in visceral adipose tissue, metabolic parameters, glucose and insulin tolerance, adipose and liver histology, adipokine and cytokine production were examined. Hyperinsulinemic-euglycemic clamp study was also performed to assess systemic insulin sensitivity. Peritoneal injection of clodronate liposomes significantly reduced blood glucose and insulin levels in DIO mice. Systemic glucose tolerance and insulin sensitivity were mildly improved in both lean and DIO mice treated with clodronate liposomes by intraperitoneal (i.p.) injection. Hepatosteatosis was dramatically alleviated and suppression of hepatic glucose output was markedly increased in DIO mice treated with clodronate liposomes. Macrophage content in visceral adipose tissue of DIO mice was effectively decreased without affecting subcutaneous adipose tissue. Interestingly, levels of insulin sensitizing hormone adiponectin, including the high molecular weight form, were significantly elevated in circulation. CONCLUSIONS/SIGNIFICANCE: Intraperitoneal injection of clodronate liposomes reduces visceral adipose tissue macrophages, improves systemic glucose homeostasis and insulin sensitivity in DIO mice, which can be partially attributable to increased adiponectin levels.